A waterfowl seed‐dispersal network from the Neotropical region is nested and modular. (11th February 2023) - Silva, Giliandro G.; Pizo, Marco Aurélio; Green, Andy J.; Sebastián‐González, Esther; Bugoni, Leandro; Maltchik, Leonardo
Abstract: Seed dispersal by vertebrates is fundamental for the persistence of plant species, forming networks of interactions that are often nested and modular. Networks involving angiosperms and frugivorous birds are relatively well‐studied in the Neotropical region, but there are no previous studies of networks involving waterbirds. Here, we describe the structure of a Neotropical waterfowl seed‐dispersal network and identify the species that have an important role for the network structure. We used information on 40 plant taxa found in fecal samples of five common waterfowl species to calculate the nestedness (NODF), weighted nestedness (WNODF), modularity, and weighted modularity of the network. We found that the network was nested, with yellow‐billed teal showing the highest contribution both to nestedness and weighted nestedness. Twenty‐four plant species contributed positively to weighted nestedness, with Salzmann's mille graines presenting the highest influence both to nestedness and weighted nestedness. The network was modular, but the weighted modularity was not significant. These results need to be considered with caution due to incomplete interaction sampling for two species. Ringed teal, Brazilian teal, and yellow‐billed teal were considered hub modular species. Among plants, beak sedges and water snowflake were considered modular hub species, while Salzmann's mille graines and spikerush were network connectors. The structure of this Neotropical waterbird seed‐dispersal network differed from the only previous waterfowl network study, from Europe, which found similar level of nestedness but no significant modularity. We include several possible explanations for this discrepancy and identified priorities for future research into waterbird–plant interaction networks. Abstract in Portuguese is available with online material. Abstract : Representation of the bipartite networks between waterfowl and plant species in a Neotropical wetland landscape. Abstract: A dispersão de sementes por vertebrados é fundamental para a persistência das espécies vegetais, sendo estas relações geralmente ocorrendo na forma de redes de interações muitas vezes aninhadas e modulares. Redes envolvendo angiospermas e aves frugívoras são relativamente bem estudadas na região Neotropical, mas inexistem estudos de redes envolvendo aves aquáticas. Neste trabalho nós descrevemos a estrutura de uma rede de dispersão de plantas por aves aquáticas neotropicais e identificamos as espécies com funções importantes para a estrutura da rede. Nós utilizamos informações sobre 40 táxons vegetais encontrados em amostras fecais de cinco espécies de aves aquáticas comuns na região neotropical para calcular o aninhamento (NODF e WNODF) e a modularidade da rede. A rede estudada se mostrou aninhada, com a marreca Anas flavirostris mostrando a maior contribuição para o NODF e WNODF. Vinte e quatro espécies de plantas contribuíram positivamente para o aninhamento, com Oldenlandia salzmannii apresentando a maior influência para NODF e WNODF. A rede se mostrou modular, embora a modularidade ponderada não tenha sido significativa. Esses resultados precisam ser considerados com cautela devido à amostragem de interação incompleta para duas espécies de aves. As marrecas Amazonetta brasiliensis, A . flavirostris e Callonetta leucophrys foram consideradas espécies hub‐modulares. Entre as plantas, Rynchospora sp e os Nymphoides indica foram considerados espécies hub‐modulares, enquanto Eleocharis bonariensis e O . salzmannii foram classificadas como conectores de rede. A estrutura desta rede de dispersão diferiu do único estudo similar disponível, da Europa, que encontrou nível semelhante de aninhamento, porém sem modularidade significativa. Nós incluímos várias explicações possíveis para essa diferença e identificamos prioridades para pesquisas futuras sobre redes de interação entre aves aquáticas e plantas.